Confused Connections? Targeting White Matter to Address Treatment Resistant Schizophrenia - Crocker, Candice E.; Tibbo, Philip G. (Frontiers in Pharmacology, 2018)
Despite development of comprehensive approaches to treat schizophrenia and other psychotic disorders and improve outcomes, there remains a proportion (approximately one-third) of patients who are treatment resistant and will not have remission of psychotic symptoms despite adequate trials of pharmacotherapy.  This level of treatment response is stable across all stages of the spectrum of psychotic disorders, including early phase psychosis and chronic schizophrenia.  Our current pharmacotherapies are beneficial in decreasing positive symptomology in most cases, however, with little to no impact on negative or cognitive symptoms. Not all individuals with treatment resistant psychosis unfortunately, even benefit from the potential pharmacological reductions in positive symptoms.  The existing pharmacotherapy for psychosis is targeted at neurotransmitter receptors.  The current first and second generation antipsychotic medications all act on dopamine type 2 receptors with the second generation drugs also interacting significantly with serotonin type 1 and 2 receptors, and with varying pharmacodynamic profiles overall.  This focus on developing dopaminergic/serotonergic antipsychotics, while beneficial, has not reduced the proportion of patients experiencing treatment resistance to date.  Another pharmacological approach is imperative to address treatment resistance both for response overall and for negative symptoms in particular. Here we review the evidence that white matter abnormalities in the brain may be underlying the symptomology of psychotic disorders and propose that white matter may be a viable pharmacological target for pharmacoresistant schizophrenia.